The adequacy of existing support systems in addressing the issue of teenage pregnancies in Malaysia: a legal response - Mohd Nor, Aishah; Mohd Zin, Najibah; Che Soh @ Yusoff, Roslina (IIUM Press, International Islamic University Malaysia, 2019)
This article examines the adequacy of the current support systems in addressing the issue of teenage pregnancies in Malaysia. This study was conducted primarily through a doctrinal study of existing literature such as articles, journals and reports related to the current issues encountered by the pregnant teenagers. There is also anon-doctrinal method carried out whereby the researchers had conducted fieldwork interviews with the government department, non-government organisations (NGOs) and social activist on the efforts done in addressing the problem. Due to the lack of a specific policy on teenage pregnancies in Malaysia, there have been concerns on issues related to the rights of these teenagers to education during pregnancy; criminal issues on abortion, infanticide and child sexual grooming; child marriages and the lack of support from parents,family members and the society for care, motivation, healthcare and preparation for motherhood among these teenagers. The findings establish the current support system is inadequate to meet the contemporary needs of pregnant teenagers. It is suggested that a comprehensive legal framework for teenage pregnancies in Malaysia needs to be put in place. These can include legislating necessary laws and policies,which can be more effective through integrated services and proper monitoring and enforcement in order to meet the current needs of the targeted group.